2017
DOI: 10.21010/ajtcam.v14i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Potential of Stem Bark Extract of Bombax Ceiba Collected Locally From South Punjab Area of Pakistan

Abstract: Background: Ethnic medication systems have been used extensively by humans since their origin. Now a day, in the developing countries these systems are being used due to their effectiveness and affordability. Especially inhabitants of rural areas still rely on these systems as first line of treatment against diseased conditions. Till now, majority of medicines is derived from the natural origin particularly plants owing to their little side effects and cost effectiveness. Materials and Methods:In the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Different parts of this plant are reported to have therapeutic potentials against different diseases such as diabetes, hepatic toxicity, infections, asthenia, polyurea and glycosuria [9][10][11][12]. Although different parts of B. ceiba are known to have different biological activities including antioxidant, antimicrobial, anti-inflammatory and analgesic, ,hypotensive and hypoglycemic activity, very little work has been done by taking an ethanolic extract of young roots of B. ceiba (BCYR) on diabetes and hepatic toxicity [9,10,[13][14][15]. Therefore, the present study was undertaken to investigate the effects of the BCYR on diabetes and hepatic toxicity in Alloxan-Induced Diabetic Mice (AIDM).…”
Section: Introductionmentioning
confidence: 99%
“…Different parts of this plant are reported to have therapeutic potentials against different diseases such as diabetes, hepatic toxicity, infections, asthenia, polyurea and glycosuria [9][10][11][12]. Although different parts of B. ceiba are known to have different biological activities including antioxidant, antimicrobial, anti-inflammatory and analgesic, ,hypotensive and hypoglycemic activity, very little work has been done by taking an ethanolic extract of young roots of B. ceiba (BCYR) on diabetes and hepatic toxicity [9,10,[13][14][15]. Therefore, the present study was undertaken to investigate the effects of the BCYR on diabetes and hepatic toxicity in Alloxan-Induced Diabetic Mice (AIDM).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic potentials against various diseases such as diabetes, infections, asthenia, polyurea, glycosuria and hepatic toxicity are reported in different parts of this plant. Although various portions of B. ceiba has different therapeutic activities, including hypoglycemic, antiinflammatory, analgesic, antioxidant, antimicrobial and hypotensive activity, but only little research has been reported to evaluate the effect of ethanolic extract of B. ceiba young roots on diabetes and liver toxicity (Rehman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1A is a compound of the saponin group which has been isolated from Jatropha tanjorensis 21 , Annona reticulata L. 22 , Abroma augusta 23, and play a role in prostate cancer 24 and protects the human hepatic LO2 cells 25 . In this study, we report the isolation of a taraxerol (1) and β-sitosterol glucoside (2) from EtOH extract of leaves.…”
mentioning
confidence: 98%